2015
DOI: 10.1111/tpj.12750
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CYC/TB1 class of TCP transcription factors in basal angiosperms and magnoliids

Abstract: SUMMARYFlower monosymmetry contributes to specialized interactions between plants and their insect pollinators. In the magnoliids, flower monosymmetry is exhibited only in the Aristolochiaceae (Piperales). Aristolochia flowers develop a calyx-derived monosymmetric perianth that enhances pollination success by a flytrap mechanism. Aristolochia arborea forms additionally a special perianth outgrowth that mimics a mushroom to attract flies, the mushroom mimicry structure (MMS). In core eudicots, members of the CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 63 publications
(119 reference statements)
5
59
0
2
Order By: Relevance
“…TCP effect on floral development was shown in a wide range of plant species, including Arabidopsis , Antirrhinum, annual candytuft ( Iberis amara ) (Busch and Zachgo, 2007; Busch et al, 2012), angiosperms like Aristolochia arborea and Saruma henryi (Horn et al, 2015), Gerbera species (Broholm et al, 2008), rice (Yuan et al, 2009), sunflowers (Fambrini et al, 2012), peas (Wang et al, 2008), ragworts (Kim et al, 2008), Morrow’s honeysuckle ( Lonicera morrowii ) (Howarth and Donoghue, 2006), Knautia macedonica (Berger et al, 2016), and orchids (De Paolo et al, 2015). …”
Section: Evolutionary Conserved Roles Of Tcpsmentioning
confidence: 99%
See 1 more Smart Citation
“…TCP effect on floral development was shown in a wide range of plant species, including Arabidopsis , Antirrhinum, annual candytuft ( Iberis amara ) (Busch and Zachgo, 2007; Busch et al, 2012), angiosperms like Aristolochia arborea and Saruma henryi (Horn et al, 2015), Gerbera species (Broholm et al, 2008), rice (Yuan et al, 2009), sunflowers (Fambrini et al, 2012), peas (Wang et al, 2008), ragworts (Kim et al, 2008), Morrow’s honeysuckle ( Lonicera morrowii ) (Howarth and Donoghue, 2006), Knautia macedonica (Berger et al, 2016), and orchids (De Paolo et al, 2015). …”
Section: Evolutionary Conserved Roles Of Tcpsmentioning
confidence: 99%
“… Phylogenetic tree of plant species in which TCP transcription factors are involved in branching (Takeda et al, 2003; Aguilar-Martínez et al, 2007; Poza-Carrión et al, 2007; Bai et al, 2012; Braun et al, 2012; Drummond et al, 2015; Nicolas et al, 2015; Muhr et al, 2016) (blue dots), flower development (Linnaeus and Rudberg, 1744; Keeble et al, 1910; Corley et al, 2005; Costa et al, 2005; Busch and Zachgo, 2007; Broholm et al, 2008; Kim et al, 2008; Nag et al, 2009; Yuan et al, 2009; Howarth et al, 2011; Busch et al, 2012; Tähtiharju et al, 2012; Claßen-Bockhoff et al, 2013; Juntheikki-Palovaara et al, 2014; De Paolo et al, 2015; Horn et al, 2015; Lucero et al, 2015; Wang et al, 2008; Wang X.et al, 2015; Yang et al, 2015; Berger et al, 2016) (purple dots) or leaf development (Kosugi and Ohashi, 1997; Nath et al, 2003; Palatnik et al, 2003; Koyama et al, 2007, 2010a,b; Ori et al, 2007; Efroni et al, 2008; Kieffer et al, 2011; Mimida et al, 2011; Sarvepalli and Nath, 2011; Danisman et al, 2012, 2013; Aguilar-Martínez and Sinha, 2013; Burko et al, 2013; Tao et al, 2013; Zhou et al, 2013; Ballester et al, 2015; Huang and Irish, 2015; Ma et al, 2016) (green dots), respectively. The phylogenetic tree was created using Phylotree and iTOL (Letunic and Bork, 2016).…”
Section: Evolutionary Conserved Roles Of Tcpsmentioning
confidence: 99%
“…Nicolas and Cubas 2016). More precisely, they belong to the class II CYC/TB1 subclade that seems to originate in the ancestor of angiosperms (Horn et al 2015). RADIALIS (RAD) and DIVARICATA (DIV) belong to another family of transcription factor genes, the MYB family.…”
mentioning
confidence: 99%
“…Second from the genetic and molecular standpoints, a CYC/TB1-based candidate gene approach has been implemented over the past 25 years, exploring the orders Piperales (Magnoliidae), Zingiberales, Commelinales and Poales (Monocotyledonae), Ranunculales and Proteales (basal eudicots), Malpighiales, Fabales and Brassicales (Rosidae), and Lamiales, Dipsacales and Asterales (Asteridae) (Hileman 2014 for review; Citerne et al 2017;Horn et al 2015). These studies have revealed a complex history of duplications in the CYC/TB1 gene lineage.…”
mentioning
confidence: 99%
See 1 more Smart Citation